Adjuvant ipilimumab versus placebo after complete resection of high-risk stage III melanoma (EORTC 18071): a randomised, double-blind, phase 3 trial. Issue 5 (May 2015) - Eggermont, Alexander M M; Chiarion-Sileni, Vanna; Grob, Jean-Jacques; Dummer, Reinhard; Wolchok, Jedd D; Schmidt, Henrik; Hamid, Omid; Robert, Caroline; Ascierto, Paolo A; Richards, Jon M; Lebbé, Céleste; Ferraresi, Virginia; et al.
Summary: Background: Ipilimumab is an approved treatment for patients with advanced melanoma. We aimed to assess ipilimumab as adjuvant therapy for patients with completely resected stage III melanoma at high risk of recurrence. Methods: We did a double-blind, phase 3 trial in patients with stage III cutaneous melanoma (excluding lymph node metastasis ≤1 mm or in-transit metastasis) with adequate resection of lymph nodes (ie, the primary cutaneous melanoma must have been completely excised with adequate surgical margins) who had not received previous systemic therapy for melanoma from 91 hospitals located in 19 countries. Patients were randomly assigned (1:1), centrally by an interactive voice response system, to receive intravenous infusions of 10 mg/kg ipilimumab or placebo every 3 weeks for four doses, then every 3 months for up to 3 years. Using a minimisation technique, randomisation was stratified by disease stage and geographical region. The primary endpoint was recurrence-free survival, assessed by an independent review committee, and analysed by intention to treat. Enrollment is complete but the study is ongoing for follow-up for analysis of secondary endpoints. This trial is registered with EudraCT, number 2007-001974-10, and ClinicalTrials.gov, number NCT00636168 . Findings: Between July 10, 2008, and Aug 1, 2011, 951 patients were randomly assigned to ipilimumab (n=475) or placebo (n=476), all of whom were included in the intention-to-treat analyses. At a median follow-up of 2·74 years (IQR 2·28–3·22), there were 528 recurrence-free survival events (234 in the ipilimumab group vs 294 in the placebo group). Median recurrence-free survival was 26·1 months (95% CI 19·3–39·3) in the ipilimumab group versus 17·1 months (95% CI 13·4–21·6) in the placebo group (hazard ratio 0·75; 95% CI 0·64–0·90; p=0·0013); 3-year recurrence-free survival was 46·5% (95% CI 41·5–51·3) in the ipilimumab group versus 34·8% (30·1–39·5) in the placebo group. The most common grade 3–4 immune-related adverse events in the ipilimumab group were gastrointestinal (75 [16%] vs four [<1%] in the placebo group), hepatic (50 [11%] vs one [<1%]), and endocrine (40 [8%] vs none). Adverse events led to discontinuation of treatment in 245 (52%) of 471 patients who started ipilimumab (182 [39%] during the initial treatment period of four doses). Five patients (1%) died due to drug-related adverse events. Five (1%) participants died because of drug-related adverse events in the ipilimumab group; three patients died because of colitis (two with gastrointestinal perforation), one patient because of myocarditis, and one patient because of multiorgan failure with Guillain-Barré syndrome. Interpretation: Adjuvant ipilimumab significantly improved recurrence-free survival for patients with completely resected high-risk stage III melanoma. The adverse event profile was consistent with that observed in advanced melanoma, but at higher incidences in particular for endocrinopathies. The risk–benefit ratio of adjuvant ipilimumab at this dose and schedule requires additional assessment based on distant metastasis-free survival and overall survival endpoints to define its definitive value. Funding: Bristol-Myers Squibb.